Strategy and Portrait of the Literacy Movement in Public Madrasah Ibtidaiyah - Wibowo, Tri; Syifana, Maswah (Faculty of Tarbiyah Universitas Islam Tribakti Lirboyo Kediri, 2023)
The need for literacy in the era of globalization demands the state's role to facilitate educational systems and services in line with the mandate of the 1945 Constitution. Efforts were made by the Ministry of Religious Affairs of the Republic of Indonesia by launching the Madrasah Literacy Movement (GLM) program to generate literacy at various levels of religious educational institutions. The research method uses qualitative research methods using a field research approach. Data was collected based on observations, interviews, and documentation. Data analysis techniques using the Miles and Huberman model go through three steps: data condensation, data presentation, conclusion, and verification. The results showed that madrasah policies in adopting the madrasah literacy movement program in Public Islamic Elementary Schools (Madrasah Ibtidaiyah Negeri, MIN) were implemented by making policies for monitored reading programs, reading corner programs, and providing textbooks/non-lessons for students. The strategy of the madrasah literacy movement in MIN is the form of conditioning a literacy-friendly physical environment, striving for a social and practical environment as a communication and literacy interaction model, and seeking madrasah as a literate academic environment. Portrait of madrasah literacy movement in awakening literacy culture in MIN through planning, habituation, development, and learning activities of literacy programs.